Effect of asymptomatic vestibular dysfunction on insomnia - Pan Gu; Yuchuan Ding; Lang Ji; Jing Feng; Huimin Fan; Tariq Kermalli; Lipeng Cai; Bo Pang; Xiaokun Geng (Environmental Disease)
Objectives: Insomnia is a common condition with limitations in treatment through cognitive behavioral or pharmacological therapies, including variable efficacy, side effects, and time commitment. Given the close association between the vestibular system and sleep regulation, this study aims to investigate whether patients with insomnia but without overt vestibular symptoms may have underlying vestibular dysfunction and whether addressing this dysfunction can ameliorate their sleep disturbances. Methods: This is a prospective, cross-sectional, and observational study that will enroll patients with chronic insomnia. Utilizing the International Classification of Sleep Disorders edition 3 for chronic insomnia diagnosis, we screen patients for exclusion of overt vestibular dysfunction via the Dizziness Handicap Inventory and rule out insomnia primarily caused by depression or anxiety using the Patient Health Questionnaire-9 and the Generalized Anxiety Disorder-7. Subjects without these conditions undergo detailed vestibular function testing, including balance and gait assessments, Videonystagmography, video head impulse test, subjective visual vertical/horizontal, and ocular/cervical vestibular evoked myogenic potential. Vestibular dysfunction will be correlated with insomnia severity as measured by the Pittsburgh Sleep Quality Index (PSQI). Results: The primary outcome measures are the presence of insomnia patients with asymptomatic vestibular dysfunction (AVD) but not OVD and the relationship between the severity of vestibular dysfunction and the severity of insomnia as indicated by PSQI scores. The secondary outcome is investigating the types and prevalence of AVD in insomnia subjects. Conclusions: This study seeks to elucidate the impact of asymptomatic vestibular dysfunction (AVD) on insomnia and understand the types and prevalence of AVD in insomnia subjects. Outcomes would potentially change the diagnostic and therapeutic paradigms toward tailored vestibular-focused rehabilitation for insomnia improvement. TRIAL REGISTRATION: www.chictr.org.cn, identifier: ChiCRT2400085439.